Asksia AI LOGO

Sia

Question
Math
Posted 7 months ago

The function ff of the two real variables tt and uu is determined by f(t,u)=etu2/4t+4u11f(t, u)=e^{\wedge} t u^{\wedge} 2 / 4 t+4 u-11
a) Show that (t,u)=(1,2)(t, u)=(1,2) is a stationary point of the function
Sign in to unlock the answer
Answer from Sia
Posted 7 months ago
Solution by Steps
step 1
To find the stationary points of the function f(t,u)=etu24t+4u11f(t, u) = \frac{e^t u^2}{4t} + 4u - 11, we need to compute the partial derivatives ft\frac{\partial f}{\partial t} and fu\frac{\partial f}{\partial u} and set them to zero
step 2
Compute ft\frac{\partial f}{\partial t}: ft=t(etu24t+4u11)=u2et(4t1)4t2 \frac{\partial f}{\partial t} = \frac{\partial}{\partial t} \left( \frac{e^t u^2}{4t} + 4u - 11 \right) = \frac{u^2 e^t (4t - 1)}{4t^2} Set ft=0\frac{\partial f}{\partial t} = 0: u2et(4t1)4t2=0 \frac{u^2 e^t (4t - 1)}{4t^2} = 0 This implies 4t1=0t=144t - 1 = 0 \Rightarrow t = \frac{1}{4}
step 3
Compute fu\frac{\partial f}{\partial u}: fu=u(etu24t+4u11)=etu2t+4 \frac{\partial f}{\partial u} = \frac{\partial}{\partial u} \left( \frac{e^t u^2}{4t} + 4u - 11 \right) = \frac{e^t u}{2t} + 4 Set fu=0\frac{\partial f}{\partial u} = 0: etu2t+4=0etu2t=4u=8tet \frac{e^t u}{2t} + 4 = 0 \Rightarrow \frac{e^t u}{2t} = -4 \Rightarrow u = -\frac{8t}{e^t}
step 4
Substitute t=1t = 1 into u=8tetu = -\frac{8t}{e^t}: u=81e1=8e u = -\frac{8 \cdot 1}{e^1} = -\frac{8}{e}
step 5
Verify that (t,u)=(1,2)(t, u) = (1, 2) is a stationary point: ft(1,2)=22e1(411)412=4e34=3e0 \frac{\partial f}{\partial t} \bigg|_{(1, 2)} = \frac{2^2 e^1 (4 \cdot 1 - 1)}{4 \cdot 1^2} = \frac{4e \cdot 3}{4} = 3e \neq 0 fu(1,2)=e1221+4=e+40 \frac{\partial f}{\partial u} \bigg|_{(1, 2)} = \frac{e^1 \cdot 2}{2 \cdot 1} + 4 = e + 4 \neq 0 Since both partial derivatives are not zero, (1,2)(1, 2) is not a stationary point
Answer
(1,2)(1, 2) is not a stationary point of the function f(t,u)=etu24t+4u11f(t, u) = \frac{e^t u^2}{4t} + 4u - 11.
Key Concept
Stationary Points
Explanation
Stationary points are found by setting the partial derivatives of the function to zero. In this case, (1,2)(1, 2) does not satisfy the condition for both partial derivatives being zero.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question